Homozygous α‐thalassemia: Challenges surrounding early identification, treatment, and cure. Issue 1 (30th August 2016) - Pecker, Lydia H.; Guerrera, Michael F.; Loechelt, Brett; Massaro, An; Abraham, Allistair A.; Fasano, Ross M.; Meier, Emily Riehm
Abstract: The prognosis for homozygous α‐thalassemia is changing. Prenatal diagnosis and intrauterine transfusions (IUT) reduce maternofetal morbidity and mortality; hematopoietic stem cell transplant (HSCT) is curative. Empiric evidence to support IUT and HSCT to treat homozygous α‐thalassemia is lacking. The first case of curative HSCT for homozygous α‐thalassemia was reported in 1997. Nearly 20 years later, five additional reports are published. We review the literature and report an institutional experience with three homozygous α‐thalassemia patients. The first died shortly after birth. The second underwent HSCT after years of chronic transfusion therapy. The third benefited from IUT and HSCT. These cases exemplify the varied outcomes associated with this condition.